Family SES, family social capital, and general health in Chinese adults: exploring their relationships and the gender-based differences - Ying Ji; Qingping Yun; Xuewen Jiang; Chun Chang (BMC, 2020)
Abstract Background Numerous studies have clarified that family socioeconomic status (SES) is positively associated with health. However, the mechanism of family SES on health needs to be further investigated from a social epidemiological perspective. This study aims to analyze the relationships among family SES, family social capital, and adult general health and tests whether gender-based differences exist in the relationship between family social capital and general health. Methods A cross-sectional survey was used to collect data from 4187 representative households in six Chinese provinces. Family SES was conceptualized based on household income, family education, and family occupational status. Family social capital was measured by using family cohesion and health-related family support. General health was assessed by using five general health perception items of the Health Survey Short Form. Structural equation modeling (SEM) was applied to examine the relationships among family SES, family social capital, and general health, and a linear regression model was used to test gender-based differences. Results The SEM showed that the direct effects of family SES, family cohesion, and health-related family support on health were 0.08 (P < 0.001), 0.17 (P < 0.001), and 0.10 (P < 0.001), respectively. Family SES had indirect effect (β = 0.05, P < 0.01) on general health via health-related family support. The total effect of family social capital (β = 0.27, P < 0.001) on general health was greater than that of family SES (β = 0.13, P < 0.001). Besides, the regression showed that the effect of health-related family support on general health was greater for women (β = 0.13, P < 0.001) than men (β = 0.04, P > 0.05). Conclusions The results provide strong support for the positive association between family SES, family social capital, and adult health. Family intervention programs should focus on establishing a harmonious family relationship to mobilize family support, particularly for the families with low cohesion and low SES.